Youth Unemployment, Labor Market Transitions, and Scarring : Evidence from Bosnia and Herzegovina, 2001-04 - Fares, Jean; Tiongson, Erwin R. (World Bank, Washington, DC, 2012)
Relatively little is known about youth unemployment and its lasting consequences in transition economies, despite the difficult labor market adjustment experienced by these countries over the past decade. The authors examine early unemployment spells and their longer-term effects among the youth in Bosnia and Herzegovina (BiH), where the labor market transition is made more difficult by the challenges of a post-conflict environment. They use panel data covering up to 4,800 working-age individuals over the 2001 to 2004 period. There are three main findings from their analysis. First, youth unemployment is high-about twice the national average-consistent with recent findings from the BiH labor market study. Younger workers are more likely to go into inactivity or unemployment and are also less likely to transition out of inactivity, holding other things constant. Second, initial spells of unemployment or joblessness appear to have lasting adverse effects on earnings and employment ("scarring"). But there is no evidence that the youth are at a greater risk of scarring, or suffer disproportionately worse outcomes from initial joblessness, compared with other age groups. Third, higher educational attainment is generally associated with more favorable labor market outcomes. Skilled workers are less likely to be jobless and are less likely to transition from employment into joblessness. But there is evidence that the penalty from jobless spells may also be higher for more educated workers. The authors speculate that this may be due in part to signaling or stigma, consistent with previous findings in the literature.